Impact of Invasive Alien Plant Species on Native Vegetation of Chhatrakot Rural Municipality, Gulmi District, Lumbini Province - Singh, Anant Gopal; Ghimire, Ram Krishna (Butwal Campus Journal, 2022)
Fieldwork was carried out in February to April 2022. The use and distribution of IAPS and their management were recorded through the application of checklists and semi-structured questionnaires Present research shows the presence of 10 invasive alien plant species from the study area. The main invasive species include Ageratina adenophora, Ageratum conyzoides, Ageratum houstonianum, Bidens pilosa, Chromolaena adorata, Parthenium hysterophorus, Mimosa pudica, Oxalis latifolia, Senna tora, and Xanthium strumarium. Bidens pilosa, one of these IAPS, is the species that is most common in agricultural areas, whereas Ageratina adenophora is the species that is most common in grasslands and forest borders. Significant IAPS in agricultural lands include Ageratum conyzoides, Ageratum houstonianum, and Oxalis latifolia, which have an immediate impact on the vegetation of the rural municipality of Chhatrakot. It was discovered that Ageratina adenophora was introduced around 20–25 years ago when road tracts were opened, despite the fact that the past of many IAPS was unknown. Ploughing, picking, burning, and composting are some common practices used to manage these IAPS in Chhatrakot rural municipality.